ROADWAY ROUGHNESS RESEARCH AND CAUSES DETERIORATION ANALYSIS - Pavlyuk, D. O.; Tereshchuk, V. P.; Chapovskyi, V. S. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The article deals with modern directions of domestic and foreign smoothness research coverage on the roads. The problem of causes changes establishing in smoothness coverage related to the irregularities in the procedure of road construction layers is highlighted. The research results of the trafficway smoothness and its causes deterioration analysis, performed by operation of roads and airfields laboratory at National Transport University on research road area H-18 around the city Buchach is shown. By the research results the road profile is drawn and the detailed analysis of road topping smoothness changes during road operation is done. Samples at the specific points on the road topping is taken: in one place it is a transverse crack, in another – without noticeable defects. It is established that road profile hollows and transverse cracks caused by black layers uneven thickness along the road.